Nanny McPhee & THE BIG BANG - Thompson, Emma; Anderson, Scoular (London, : Bloomsbury Publishing, 2010)
Nanny McPhee embarks on a brand new adventure in this brilliant, funny and captivating novel based on the new Nanny McPhee film. The Green family are trying to survive the war in their house in the country, but unfortunately they are not out of harm's way. A wicked uncle is intent on getting his hands on the family fortune and the children miss their father who is away fighting who knows where, and then the horrible cousins arrive! Life is not easy in the Green household. Thank heavens for Nanny McPhee.